Evolución de los sectores económicos y estructura empresarial del Cantón Catamayo periodo 2012-2021 - Jiménez Soto, Luz Mireya (2024)
This work presents the evolution of the economic sectors and the business structure of the Catamayo Canton in the period (2012-2021). During this period, significant changes were observed in the local economy and in the composition of the companies present in the region. It has been shown that entrepreneurship decisions in the canton are oriented towards activities focused on the service sector, such as: wholesale and retail trade, repair of motor vehicles and motorcycles, transportation, storage, communications, and highlights, that the agriculture and livestock sector are of little interest to the community. Likewise, the relevance of the manufacturing sector was highlighted as the Malca company that has generated employment and has boosted the canton's economy. Consequently, it is recommended to apply diversification as a strategic approach as it allows risk to be spread across different product lines, which can protect local companies against changes in economic conditions. Catamayo, by having all the sufficient resources to generate industries together with intelligent diversification, will cause resources to be used efficiently, improving business resilience, that is, companies or establishments are more resistant, since it is not exposed to a single sector or a single product.